IEC and Technology Transfer for Biodiversity Conservation and Utilization in Central Luzon - Paz-Alberto, Annie Melinda; Serrano, Shirly C.; Alberto, Roann P.; Ang, Janice Faye S.; Juganas, Daryl A.; Mapanao, Kathrina M.; Hernando, Princess Joy C. (Silliman Journal, 2022)
This study was conducted to enhance public awareness on the importance of biodiversity for better appreciation and participation in conservation programs and organize the local communities for meaningful participation in program activities. Training on biodiversity and nature conservation and promotion of green technology were conducted as well as technology transfer to farmers, SDU multisectoral networks, LGUs, students, and interested individuals/organizations for possible adoption. Pamphlets, brochures, and handbooks on biodiversity and nature conservation and environmental problems/issues affecting biodiversity were prepared, developed, produced, and printed for public education/ awareness. Furthermore, videos on the biodiversity of Central Luzon entitled Video on Flora and Video on Fauna in Central Luzon were also prepared, developed, and produced for environmental information and awareness. Furthermore, seminar-workshops on biodiversity conservation and utilization in Central Luzon were conducted in Carranglan, Nueva Ecija; Baler, Aurora; and Balanga, Bataan. Moreover, media linkages through print and broadcast media were undertaken for wider information dissemination. Promotional activities through different social media were also utilized including Facebook, Twitter, and Instagram. Green technology promotion and transfer were also carried out in the three study sites wherein brochures, posters, videos, and jingles on botanical pesticides and phytoremediation were promoted. Field demonstrations were also conducted to farmers, SDU multisectoral networks, LGUs, students, and interested individuals/organizations as part of the promotion and transfer of technology. The IEC materials and other promotional campaign materials are very effective and important instruments for public awareness and education. Hence, they are very potent tools in biodiversity conservation and green technology transfer for possible adoption.